2009
DOI: 10.1200/jco.2008.19.8721
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Alone and in Combination With Irinotecan in Recurrent Glioblastoma

Abstract: Bevacizumab, alone or in combination with irinotecan, was well tolerated and active in recurrent glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

65
1,709
15
24

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 2,247 publications
(1,813 citation statements)
references
References 25 publications
65
1,709
15
24
Order By: Relevance
“…aflibercept, sunitinib, vandetanib or nintedanib failed to give an efficacy signal. Cediranib, a pan-tyrosine kinase inhibitor of VEGFR achieved similar response rates and PFS-6-data as did bevacizumab in phase II [85,86,106]. The subsequent phase III trial of cediranib showed comparable but not better efficacy than lomustine.…”
Section: Targeted Therapymentioning
confidence: 90%
See 4 more Smart Citations
“…aflibercept, sunitinib, vandetanib or nintedanib failed to give an efficacy signal. Cediranib, a pan-tyrosine kinase inhibitor of VEGFR achieved similar response rates and PFS-6-data as did bevacizumab in phase II [85,86,106]. The subsequent phase III trial of cediranib showed comparable but not better efficacy than lomustine.…”
Section: Targeted Therapymentioning
confidence: 90%
“…A detailed listing of all trials with these agents, mostly conducted as single arm studies, would be beyond the scope of this review. Carboplatin (CABARET trial) and irinotecan (BRAIN trial) have been evaluated in randomized phase II trials as add-ons to bevacizumab (Table 3) [84,85]. Both trials were negative showing no difference in outcome but additional toxicity in the treatment arms with carboplatin and irinotecan.…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 99%
See 3 more Smart Citations